Fenomena Investasi Syariah Di Era Digital - Sifwatir Rif’ah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2024)
Sharia investment in the era of globalization provides profitable investment prospects as well as benefits for financial inclusion and sustainable economic development. The purpose of this study is to determine Sharia investment and its impact on digital life. The research method used is qualitative research with a data collection method of literature study, then analyzed using a descriptive analysis method. Furthermore, information from the literature study will be integrated with the research theoretical framework to help understand the complex relationship between technology and sharia investment. The results of this study are that many sharia investment instruments have been systematically followed the digitalization era. Able to create a positive impact in the financial world, increase accessibility, efficiency, and transparency. It is hoped that the sharia financial industry in Indonesia can continue to grow and provide broader benefits for the Muslim community in investing in accordance with sharia principles.